2020
DOI: 10.3389/fcimb.2020.00348
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antimicrobial Resistance Determinants in Aeromonas veronii Strain MS-17-88 Recovered From Channel Catfish (Ictalurus punctatus)

Abstract: Aeromonas veronii is a Gram-negative species ubiquitous in different aquatic environments and capable of causing a variety of diseases to a broad host range. Aeromonas species have the capability to carry and acquire antimicrobial resistance (AMR) elements, and currently multi-drug resistant (MDR) Aeromonas isolates are commonly found across the world. A. veronii strain MS-17-88 is a MDR strain isolated from catfish in the southeastern United States. The present study was undertaken to uncover the mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…In our study, resistance to florfenicol (COWT: 2 µg/mL) was found for 31 out 211 isolates (14%), which can be associated with the higher occurrence and abundance of the floR-1 efflux pump gene in NWT than in WT isolates. Our results are in line with previous authors who considered that most pathogenic bacteria in fish, including Aeromonas spp., mediate florfenicol resistance through floR [30,64]. Although β-lactam antibiotics are not used in aquaculture, blaSHV-01 was detected in 144 out of 211 (68%) Aeromonas strains in our study.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, resistance to florfenicol (COWT: 2 µg/mL) was found for 31 out 211 isolates (14%), which can be associated with the higher occurrence and abundance of the floR-1 efflux pump gene in NWT than in WT isolates. Our results are in line with previous authors who considered that most pathogenic bacteria in fish, including Aeromonas spp., mediate florfenicol resistance through floR [30,64]. Although β-lactam antibiotics are not used in aquaculture, blaSHV-01 was detected in 144 out of 211 (68%) Aeromonas strains in our study.…”
Section: Discussionmentioning
confidence: 54%
“…The current study revealed that mcr-3 genes were present in some, but not all, A. veronii genomes ( Table 2 ), indicating that A. veronii does not inherently carry the mcr-3 gene. However, A. veronii may be a reservoir for the dissemination of mcr-3 genes to other bacteria, as previously reported [ 14 , 16 ].…”
Section: Resultsmentioning
confidence: 57%
“…Thus, it has been observed that Aeromonas spp. acquire and carry antimicrobial and multi-drug resistance elements (Tekedar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%